How do you solve the system of equations:

y = 2x - 4

y = 4x - 10

y = 2x - 4

y = 4x - 10

Since both expressions are equal to y, then they are equal to each other.

2x - 4 = 4x - 10 {substituted 2x - 4, in for y, into bottom equation}

-4 = 2x - 10 {subtracted 2x from each side}

2x = 6 {added 10 to each side}

x = 3 {divided each side by 2}

y = 2x - 4 {top equation}

y = 2(3) - 4 {substituted 3, in for x, into top equation}

y = 6 - 4 {multiplied}

y = 2 {subtracted}

By the way, (3,2) is the point of intersection of the two lines when

they are graphed on a coordinate plane, as you see below:

2x - 4 = 4x - 10 {substituted 2x - 4, in for y, into bottom equation}

-4 = 2x - 10 {subtracted 2x from each side}

2x = 6 {added 10 to each side}

x = 3 {divided each side by 2}

y = 2x - 4 {top equation}

y = 2(3) - 4 {substituted 3, in for x, into top equation}

y = 6 - 4 {multiplied}

y = 2 {subtracted}

**x = 3 and y = 2**By the way, (3,2) is the point of intersection of the two lines when

they are graphed on a coordinate plane, as you see below:

*- Algebra House*